TEORI KONEKSIONISME DALAM PEMBELAJARAN BAHASA KEDUA ANAK USIA DINI - Muhammad Ali Zabidin; Indrya Mulyaningsih (Jurusan Tadris Bahasa Indonesia, 2016)
Connectionism theory view that learning occurs by experimenting and making mistakes, as well as language learning in early childhood. Each early childhood initially tries to speak and make mistakes before they become accustomed to the pronunciation and correct. Any child's vocabulary has increased and finally to convey the intent and purpose to his interlocutor well. The process can be seen from the process of learning a second language in early childhood. In second language learning is done by younger children show conformity of laws and principles of learning connectionism theory. Giving the prize being a stimulus of children to learn and motivated to recite the words proposed as a form of positive response. Reduced average number of repetitions of the first week as many as seventeen times to three times in the fourth week is a proof of principle trial and error learning proposed by Edward Thorndike. Factors second language learning is strongly influenced by age, first language, language development and motivation.Â Â